The physiological characteristics of inward rectifying potassium channel Kir4.2 and its research progress in human diseases - Zhang, Hongling; Bai, Zhongyuan; Xi, Yanfeng (Frontiers in Cell and Developmental Biology, 2025)
Kir4.2 is a member of the inward rectifying potassium channel family, encoded by the KCNJ15 gene. The Kir4.2 protein is expressed in various organs including the kidneys, liver, pancreas, bladder, stomach, and lungs. Kir4.2 not only forms functional homomeric channels, but also heteromeric channels with Kir5.1. An increasing number of studies indicate that the function of the Kir4.2 channel should not be underestimated. Kir4.2 participates in cell electrotaxis chemotaxis by sensing extracellular electric fields and functions as a K + sensor in the proximal tubules of the kidney, playing a crucial role in maintaining acid-base and potassium balance. This article provides a comprehensive review of the main physiological characteristics of the Kir4.2 channel, the various pathological processes it is involved in, and the human diseases resulting from Kir4.2 dysfunction.